Clear cell papillary renal cell carcinoma, renal angiomyoadenomatous tumor, and renal cell carcinoma with leiomyomatous stroma relationship of 3 types of renal tumors: a review - Hes, Ondrej; Compérat, Eva Maria; Rioux-Leclercq, Nathalie (Annals of diagnostic pathology, 2016)
Renal angiomyoadenomatous tumor has been described in 2000, followed by description of clear cell papillary renal cell carcinoma in 2006. Discussions about possible relationship of both tumors were published since their description. The main differential diagnostic feature was considered presence/absence of fibroleiomyomatous stroma-relationship of renal angiomyoadenomatous tumor in stroma-rich tumors. However, it was shown that stroma is reactive and nonneoplastic by its nature and that all other histologic, immunohistochemical, and molecular-genetic features of both entities are identical. In upcoming World Health Organization classification of renal tumors (2016), both lesions are considered as a single entity (clear cell papillary renal cell carcinoma [CCPRCC]). Most published cases followed the benign/indolent clinical course. In addition, most tumors has normal status of VHL gene (methylation, LOH 3p, mutations); however, CCPRCC was referred in patients with VHL syndrome. Another issue covered by this review is possible relationship of CCPRCC and "renal cell carcinoma with leiomyomatous stroma" (RCCLS). Renal cell carcinoma with leiomyomatous stroma shows clear cell cytology and abundant leiomyomatous stroma. Some of RCCLS are positive for cytokeratin 7; some are negative. Similar situation exists for relation of RCCLS and VHL gene abnormalities. It is so far unclear whether any relation between CCPRCC and RCCLS exists. From all published studies, it seems that these tumors are less likely related to each other.
Keywords: diferenciální diagnóza; Von Hippel-Lindau Tumor Suppressor Protein; Carcinoma, Renal Cell; nádorový supresorový protein VHL; Carcinoma, Papillary; Renal cell carcinoma with leiomyomatous stroma; lidé; von Hippel-Lindau Disease; keratin-7; mutace; karcinom z renálních buněk; Keratin-7; Kidney Neoplasms; Biomarkers, Tumor; nádorové biomarkery; Mutation; Humans; ledviny; Diagnosis, Differential; Clear cell papillary renal cell carcinoma; Kidney; VHL gene; von Hippelova-Lindauova nemoc; Relationship; papilární karcinom; Renal angiomyoadenomatous tumor; nádory ledvin